Interferon gene expression in sputum cells correlates with the Asthma Index Score during virus‐induced exacerbations. Issue 6 (June 2014) - Schwantes, E. A.; Manthei, D. M.; Denlinger, L. C.; Evans, M. D.; Gern, J. E.; Jarjour, N. N.; Mathur, S. K.
Summary Background The majority of asthma exacerbations are related to viral respiratory infections. Some, but not all, previous studies have reported that low interferon responses in patients with asthma increase the risk for virus‐induced exacerbations. Objective We sought to determine the relationship between lower airway inflammatory biomarkers, specifically interferon gene expression, and the severity or presence of an exacerbation in asthmatics experiencing a naturally occurring viral infection. Methods Sputum samples were analysed from subjects in an asthma exacerbation study who experienced a confirmed viral infection. Subjects were monitored for daily symptoms, medication use and peak expiratory flow rate until baseline. Sputum samples were assessed for cell counts and gene expression. Results Interferon gamma expression was significantly greater in patients with asthma exacerbations compared to non‐exacerbating patients (P = 0.002). IFN‐α1, IFN‐β1 and IFN‐γ mRNA levels correlated with the peak Asthma Index (r = 0.58, P < 0.001; r = 0.57, P = 0.001; and r = 0.51, P = 0.004, respectively). Additionally, IL‐13, IL‐10 and eosinophil major basic protein mRNA levels were greater in patients with asthma exacerbations compared to non‐exacerbating patients (P = 0.03, P = 0.06 and P = 0.02, respectively), and IL‐13 mRNA correlated with the peak Asthma Index (P = 0.006). Conclusions Our findings indicate that asthma exacerbations are associated with increased rather than decreased expression of interferons early in the course of infection. These findings raise the possibility that excessive virus‐induced interferon production during acute infections can contribute to airway inflammation and exacerbations of asthma.